Evaluation of Local Business Entity (Bumdes): Evidence From Indonesia - Yani Taufik; Lukman Yunus; Munirwan Zani; Putu Arimbawa (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
Since Law Number 6 of 2014 concerning villages, the Indonesian government has disbursed substantial funds directly to villages. One of the objectives of allocating these funds is to establish a village-owned enterprise (Bumdes). This study aims to evaluate these institutions. To assess the performance of the Bumdes, criteria, indicators, and verifiers were used following the regulations of the Minister for underdeveloped regions and transmigration of the Republic of Indonesia, Number 4 of 2015. Research carried out in 2019. Eighteen Bumdes were selected in 18 sub-districts as samples from the 113 Bumdes formed in the Konawe district. This study aims to see to what extent the existence of Bumdes has been able to contribute to improving the village economy. Respondents in this study were Bumdes stakeholders, starting from the district level (head of the Village Community Development Agency, Head of the Regional Development Planning Agency, and Head of Development), head of sub-districts, village heads, Bumdes Managements, and Community Leaders. The results showed that most of the Bumdes had not been able to properly compile business plans due to their administrators’ low human resource capacity. As a result, Bumdes capital is not developed and depends on only the allocation of village funds. The existence of Bumdes has not provided a real contribution to the increase in economic activity and village development as envisaged